Outpatient depression current care expenditure changes in Liaoning Province from 2015 to 2020: a study based on the “system of health accounts 2011” - Ma, Yuedan; Shi, Xiaoxia; Sznajder, Kristin K.; Zhao, Yue; Wan, Quan; Chai, Peipei; Yang, Xiaoshi (Frontiers in Pharmacology, 2024)
Introduction: Depression is the leading cause of disability worldwide and has become a health issue of global concern. Based on the "System of Health Accounts 2011" (SHA 2011) for patients with depression, this paper studies the changes in the current curative expenditure (CCE) of outpatient depression in Liaoning Province, China, and provides policy recommendations. Method: A stratified multistage random sample of 56,994 patients with depression included from 1,227 healthcare facilities in Liaoning Province were included. The significance of differences in variables within groups was analyzed by univariate analysis (including descriptive statistics analysis, Mann-Whitney U test and Kruskal-Wallis H test), and factors influencing depression outpatient CCE were analyzed by multiple linear regression analysis and constructing structural equation models(SEM).